Innovation in design methodology applied to surface design facing fashion (ModaPalavra e-periódico, 2016)
This article discusses the use of Creative Logical tool (NDS -UFRGS), developed to innovate teaching methods applied to design,as a stimulus for the creative process of surface design products. The tool was used to design the collection " Rips” and it stimulated the combination of manual and digital techniques to create modules and visual textures aiming to obtain unique and unusual prints. This study also highlights the importance of aligning the creation and the transfer process of the image to fabric. As a result, the article demonstrates that the combination of methods, both manual and digital, alongside the Creative Logical tool can enhance innovation in terms of surface design focused on fashion and the importance of adapting the project to the printing processes available nowadays.
Keywords: surface design; creative logic and manual and digital methods